A Tunable Multifunctional Terahertz Asymmetric Transmission Device Hybrid With Vanadium Dioxide Blocks - Xu, Boli; Zhong, Renbin; Liang, Zekun; Fang, Zheng; Fang, Jianhui; Zhang, Huimin; Wu, Zhenhua; Zhang, Kaichun; Hu, Min; Liu, Diwei (Frontiers in Materials, 2022)
A tunable multifunctional terahertz metamaterial asymmetric transmission device is proposed. The device is composed of three layers from top to bottom, i.e., Ge–SiO2–Ge. The germanium layer with a VO2 block enables it to work in two operating modes by controlling the state of the VO2 blocks, thereby flexibly realizing asymmetric forward and backward transmission with specific polarization. The device is endowed with a more flexible design of electromagnetic systems, rendering it suitable for applications in polarization converters, polarization filters, and other polarization modulators.